2008
DOI: 10.1007/s10585-008-9143-9
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases stimulate epithelial-mesenchymal transition during tumor development

Abstract: Matrix metalloproteinases (MMPs) are a family of more than 28 enzymes that were initially identified on the basis of their ability to cleave most elements of the extracellular matrix (ECM) but have subsequently been found to be upregulated in nearly every tumor type. As digestion of the ECM is essential for tumor invasion and metastasis, MMPs have been studied for their role in these later stages of tumor development. More recently, exposure to these enzymes has been found to impact cellular signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
157
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(164 citation statements)
references
References 80 publications
(73 reference statements)
6
157
0
1
Order By: Relevance
“…More recently, Orlichenko and Radisky, have shown a similar effect for MMP-9 but not MMP-2. 36 We did not observe changes in Snail expression in C57MG and C57MG/Wnt1 cells in the absence or presence of AG3340 (data not shown) suggesting therefore a different mechanism. 37,38 The mechanism by which MMP-3 regulates Wnt signaling in C57MG cells is presently unknown but currently investigated in our laboratory.…”
Section: Preventive Treatment With Mmp Inhibitor Prevents and Delays mentioning
confidence: 70%
“…More recently, Orlichenko and Radisky, have shown a similar effect for MMP-9 but not MMP-2. 36 We did not observe changes in Snail expression in C57MG and C57MG/Wnt1 cells in the absence or presence of AG3340 (data not shown) suggesting therefore a different mechanism. 37,38 The mechanism by which MMP-3 regulates Wnt signaling in C57MG cells is presently unknown but currently investigated in our laboratory.…”
Section: Preventive Treatment With Mmp Inhibitor Prevents and Delays mentioning
confidence: 70%
“…MMPs, which are secreted from both tumor and/or stroma cells, play a role in tumor invasion and metastasis by degrading the extracellular matrix (ECM) surrounding the tumor, especially the basement membranes (28). Emerging evidence indicates that MMPs can stimulate processes associated with EMT to enhance tumor cell invasion and metastasis potential (29). Most reports have suggested that predominant expression of MMP-2, -3 and -9 proteins is correlated with a poorer prognosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…As a class of proteins, MMP proteases have essential roles in the regulation of invasion, as well as important roles in motility and adhesion, through their ability to degrade extracellular matrix (ECM) proteins (33). While important in the healing response, MMP proteins are often de-regulated in cancers and can lead to increased invasion and metastasis (33). We observed, through zymography, that CCL2 increased MMP-9 activity, but not MMP-2 in PC-3 cells and this up-regulation was blocked by curcumin (Fig.…”
Section: Discussionmentioning
confidence: 99%